LIBRARY SERVICES AND CUSTOMER SATISFACTION IN STATE UNIVERSITIES AND COLLEGES IN THE BICOL REGION - Oloteo, Rolando; Mabesa, Jr., Henry (Journal of Philippine Librarianship, 2014)
This paper discusses the assessment of library services of eight State Universities and Colleges in the Bicol Region for school year 2010-2011. The assessment covered the following aspects: (1) the profile of library services of state universities and colleges; (2) effectiveness of the library services; (3) customer satisfaction on library services; (4) performance of State Universities and Colleges on accreditation and SUC level; (5) customer satisfaction; and (6) relationship between effectiveness of library services and customer satisfaction. The descriptive-evaluative and correlational methods of research were employed. The data were obtained through questionnaire, documentary analysis and interviews. The results of the test revealed that there were no significant correlations between the predictor variable effectiveness along circulation/interlibrary loan, collection development, reference/information and cataloging and indexing as well as outcome variable performance along accreditation status and SUC Level.
Keywords: Bicol region; state colleges and universities; user satisfaction